A novel energy consumption approach to extend the lifetime for wireless sensor network. (12th January 2021) - Jerbi, Wassim; Guermazi, Abderrahmen; Trabelsi, Hafedh
The deployment of the WSN provides a non-uniform distribution in the surveyed area. This we offer low-density clusters and high-density clusters. Clusters that cover a limited number of nodes are quickly exhausted. This due to the load occupied by these nodes throughout the network operation. Many times these nodes will be elected as a CH, they consume more energy. Faced with this unbalanced repartition between clusters, we proposed a routing protocol 'coverage protocol to connected nodes' (CPCN) to improve the connectivity between nodes guarantee full coverage and ensure quality of service (QoS of the WSNs). Our proposed CPCN protocol is compared to other MCSL, TQCML-EM and HESL protocols with the TOSSIM simulator was an effective solution to extend network life by minimising power consumption.